Strength and physical properties of concrete brick at elevated temperature - N I M, Yassin; S H, Adnan; S, Shahidan; S S, Ayop
This paper discusses the strength and physical properties of lightweight concrete brick before and after being exposed to fire. For this study, lightweight concrete brick was made up of cement, sand, expanded polystyrene (EPS) and palm oil fuel ash (POFA). EPS and POFA are replacement materials used as sand and cement replacement respectively. The percentage of replacement materials was varied, which 0%, 20%, 30%, 40% and 50% for EPS and 0%, 10% and 25% for POFA. The strength and physical properties of bricks were observed and tested before and after being exposed to elevated temperature. Fire performance test of bricks was tested using electronic furnace where the temperature of fire was 300oC, 500oC and 700oC with heating rate 10oC/min. The duration of fire test was conducted for 2 hours. Among the physical properties that have been observed are deformation of shape, discolouration and surface cracking of brick samples. Generally, the brick strength were decreased as the percentage of materials replacement increase. The reduction of strength was continued when bricks were exposed to high temperature. However, the strength of the bricks was fluctuated when been exposed to different temperature.